ANALISIS SISTEM PEMPROSESAN TRANSAKSI PADA SIKLUS REVENUE PT SIG - Arthaingan H. Mutiha (Jurnal Vokasi Indonesia, 2014)
Good accounting information system is information system that can generate accurate, on time and reliable information for management decision making.  The use of database  to keep the financial transaction  and operasional transaction data must be integrated.  Integrated database will avoid redundant data and keep the currency of data.  Single database in each division will be time consuming, expensive and will cause inconsistency of data.  This will be the disadvantage for the company to compete.  PT SIG is the company operating in freight forwarding industry.  One of the main responsibility is to manage the delivery of package from one place to another place all over the world and to manage all documents related to the shipping.  The management of documents in this industry is very complex, therefore the need to handle the documents in the efficient, complete, fast and zero errror is the prime need of the management.  The documents distributed in this industry are  complex.  The shipment of the package can be performed if the whole documents are complete.  Unfortunatelly, the company can not manage its documents efficiently and effectively.  Documents are manually generated and also manually distributed.  The analysis in this research is the modelling process analyis that will become the basis for the designing of the system.  Modelling process used in this research is Data Flow Diagram.  The analysis of Information System of PT SIG is capable of giving some recomendation to solve the company problem in getting data accuratelly,on time and also to give the best service to  the customer The reliable accounting information system is the system that can generate accurate, on time and reliable information for management decision making and to serve customer in a better way.Keyword : analysis information system, proces modelling, data flow diagram